The relationship between cognition and depressive symptoms, and factors modifying this association, in Alzheimer's disease: A multivariate multilevel model. (September 2017) - Yang, Bei; Yu, Hongmei; Xing, Min; He, Runlian; Liang, Ruifeng; Zhou, Liye
Highlights: We explored correlations between MoCA and GDS-30 in AD and modifying factors. Four waves of assessment of 104 patients with AD were conducted between 2010 and 2012. More severe depression predicted rapid decline in cognition, and vice versa. Specific factors affecting cognition and depression are critical to AD progression. Abstract: Objectives: To examine whether there was a bidirectional association between cognition and depressive symptoms in Alzheimer's disease (AD), and to explore the role of socio-demographic factors and daily performance in this association. Methods: We conducted a longitudinal study of 104 community-dwelling patients with confirmed AD from Taiyuan, China. We assessed cognition and depressive symptoms (dependent variables) with the Montreal Cognitive Assessment (MoCA) and the Geriatric Depression Scale-30 (GDS-30), respectively. Socio-demographic information and daily performance were treated as explanatory variables. A multivariate multilevel model was built to investigate the interrelationship between patients' cognition and depression, as well as the effect of related factors on both outcomes. Results: MoCA scores were negatively correlated with GDS-30 both at the subject level (correlation coefficient r 3 = −0.68, χ 2 = 19.26, P < 0.001) and time point level ( r 2 = −0.35, χ 2 = 35.68, P < 0.001) in patients with AD. Multivariate analysis showed several significant factors for cognitive function, including educational level, personality, hobbies, exercise, reading, aluminum utensil use, dietary restriction and hypertension (regression coefficients: 0.60, 0.52, 0.51, 0.48, 0.45, −0.48, 0.67, and −0.74, respectively). Significant factors for depressive symptoms included family status, employment before retirement, homemaking, reading, aluminum utensil use, dietary restriction, and hypertension (regression coefficients: 3.09, −1.33, −1.62, −1.31, 0.96, −1.15, and 1.14, respectively). Conclusion: These findings indicated that cognition was negatively associated with depression in patients with AD, and both were influenced by reading, aluminum utensil use, dietary restriction, and hypertension. Considering patient factors may help to slow the progression of dementia.